Peran Ayah dalam Keberhasilan Program Inisiasi Menyusui Dini (IMD) pada Bayi Yang Lahir secara Sectio Cesaria - Sestu Retno D. A.; Nursalam Nursalam; Budi Santoso; Rachmat H. (Jurnal Ners, 2016)
Introduction: Delivery through Sectio Caesaria (SC) is one of the obstacles to doing Initiation of Breast Feeding. The readiness of new mothers to give her milk to the newborns in need of psychological preparation, because the mother has a role change. The achievement of the role of the mother can be successful if the mother close to the baby and get the support from the spouse (husband). Husband's role in the implementation of IMD is very important. Husband's involvement in the implementation of IMD include the provision of support and interaction. The husband is the closest person for breastfeeding mothers who are expected to always be on the maternal side, and are always ready to provide assistance. If mothers gain confidence and full support of her husband, the motivation for breastfeeding mothers will increase.The objective of this study was to know the role of husband in accompanied the mother with section caesarean in implementing of IMD.Methods: This study used observational eksplanatif, with cross-sectional design, the aims were collecting the respondent data to answer the strategic issues which were going on, which caused the post SC women do not implemented the IMD. Respondent: as many 282 post SC mothers who covered the inclusion and exclusion criteria. The study was conducted in the operating room (OK) Type B obstetrics hospitals, namely RSUD Jombang and RSUD Sogaten Madiun.Result: The test results Together showed there was an effect from Spouse support variable and spouse’s interaction to the implementation of IMD. Individual test result of spouse support to the effect of implementation of IMD, however variable of spouse’s interaction, there was no effect to the implementation of IMD. The implementation of IMD was effected by spouse support as many as 3,7%.Discussion:The mother that had the support from spouse had a higher motivation in implementation of IMD to the baby.